Studi Yuridis Tentang Kewenangan Dokter Anestesi dalam Penetapan Do Not Resuscitate (DNR) pada Operasi Risiko Tinggi - I Komang Agus Tri Wismantara; Aris Prio Agus Santoso; Rina Arum Prastyanti (Lembaga Pengembangan Kinerja Dosen, 2026)
Bioethical and legal dilemmas arise when a Do-Not-Resuscitate (DNR) status is applied within the context of high-risk surgery, where anesthesia inherently depresses vital functions in a manner mimicking cardiac arrest. This study aims to analyze the juridical basis of the anesthesiologist's authority in determining or suspending DNR status in the operating room, as well as its legal implications for medical liability and patient autonomy. This study employs a normative juridical research method utilizing a statute approach and a conceptual approach. Secondary data sources are derived from legislation regarding medical practice, health laws, and medical ethics literature. The findings indicate that the anesthesiologist's authority regarding DNR in high-risk surgeries is not absolute but is contingent upon the principle of required reconsideration. Juridically, anesthesiologists possess discretionary authority to perform limited resuscitation if cardiac arrest is induced by the anesthetic procedure (iatrogenic) rather than the natural progression of a terminal illness, to prevent malpractice and wrongful death claims. However, the absence of specific regulations governing